Fascist visions : art and ideology in France and Italy - Affron, Matthew, 1963-; Antliff, Mark, 1957- (Princeton, N.J. : Princeton University Press, 1997)
Bringing together studies by art historians, historians, and political scientists, Fascist Visions explores the themes and paradigms that pervaded protofascist and fascist aesthetic discourse, cultural policy, and artistic production in France and Italy. Whether traditionalist or innovative in idiom, art expressed fascism's ideological polarities: nihilism and idealism, modernism and antimodernism, revolution and reaction. This volume charts the unfolding of fascist aesthetics from its genesis in nationalist and antimaterialist ideologies before World War I to its full development during the interwar period and World War II. It also highlights the shared motivations of advocates of fascist aesthetics, including artists, art critics, political activists, and government officials, outside of Germany.
Art and fascist ideology in France and Italy: an introduction / Matthew Affron and Mark Antliff -- Myth of national regeneration in Italy: from modernist avant-garde to fascism / Emilio Gentile -- Ardengo Soffici and the religion of art / Walter L. Adamson -- Valentine de Saint-Point and the fascist construction of woman / Nancy Locke -- Cite francaise: Georges Valois, Le Corbusier, and fascist theories of urbanism / Mark Antliff -- Waldemare George: a parisian art critic on modernism and fascism / Matthew Affron -- State as patron: making official culture in fascist Italy / Marla Stone -- Decadence and renewal in the decorative arts under Vichy / Michele C. Cone.
Includes bibliographical references (pages 263-273) and index.
Print version record.
JSTOR
Keywords: Le Corbusier -- 1887-1965; Saint-Point, Valentine de -- 1875-1953; Sironi, Mario -- 1885-1961; Soffici, Ardengo -- 1879-1964; Valois, Georges -- 1878-1945; Soffici, Ardengo; Saint-Point, Valentine de; Sironi, Mario; Valois, Georges; Le Corbusier; Fascism and art -- France; Art and state -- France; Fascism and art -- Italy; Art and state -- Italy; Fascisme et art -- France; Art -- Politique gouvernementale -- France; Fascisme et art -- Italie; Art -- Politique gouvernementale -- Italie; 20.10 art and society: general; ART -- Individual Artists -- General; Art and state; Fascism and art; France; Italy; Faschismus; Kunst; Kunstpolitik; Frankreich; Italien; Vichy-Regime; Aufsatzsammlung; Kunst; Fascisme; Fascism and art -- France; Fascism and art -- Italy; Art and state -- France -- History -- 20th century; Art and state -- Italy -- History -- 20th century; France; Italy; Fascism; Cultural property; Cultural heritage; Art et État -- Italie; Fascisme et art -- Italie; Aufsatzsammlung